1990
DOI: 10.1056/nejm199005103221901
|View full text |Cite
|
Sign up to set email alerts
|

2′,3′-Dideoxyinosine (ddI) in Patients with the Acquired Immunodeficiency Syndrome or AIDS-Related Complex

Abstract: 2',3'-Dideoxyinosine (ddI) is a purine analogue that after intracellular metabolic conversion suppresses the replication of the human immunodeficiency virus (HIV). We conducted a Phase I dose-escalation study of ddI in 17 patients with the acquired immunodeficiency syndrome (AIDS) and 20 patients with AIDS-related complex. The drug was administered twice daily over a dose range of 0.4 to 66 mg per kilogram of body weight per day for 2 to 44 weeks. The maximal tolerated oral dose of ddI was estimated to be 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
4

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 371 publications
(95 citation statements)
references
References 18 publications
2
89
0
4
Order By: Relevance
“…Systemic availability appears to be further compromised by a rate-limited absorption step (8,12,14), leading to recommendations that ddI be taken BID instead of once a day (3a, 8). With the ddI formulations used in this trial (taken BID under fasting conditions), mean systemic bioavailability has been reported to range from 33 to 41% (8,14,15,18,22). Since the AUC of ddI has been shown to correlate with both suppression of p24 antigen and the frequency of adverse effects (7,8,22), a prospective study to evaluate whether monitoring concentrations in serum improves response or reduces toxicity may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic availability appears to be further compromised by a rate-limited absorption step (8,12,14), leading to recommendations that ddI be taken BID instead of once a day (3a, 8). With the ddI formulations used in this trial (taken BID under fasting conditions), mean systemic bioavailability has been reported to range from 33 to 41% (8,14,15,18,22). Since the AUC of ddI has been shown to correlate with both suppression of p24 antigen and the frequency of adverse effects (7,8,22), a prospective study to evaluate whether monitoring concentrations in serum improves response or reduces toxicity may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50 to 70% of the absorbed dose of ddI appears in urine as various metabolites, although the full metabolic profile is unknown (3a, 11a, 14). Dose-related toxicities of ddI include peripheral neuropathy and pancreatitis (5,15,22). Since fluconazole and ddI are commonly coadministered, fluconazole has the potential to inhibit the metabolism of ddI, leading to higher levels in serum and an increase in toxicities or intolerance.…”
mentioning
confidence: 99%
“…In Caucasians, there is an association between ODM and uveal melanoma. 1,2 The disease, on the other hand, is rare in blacks. We report here a case of ODM and uveal melanoma in a black patient.…”
Section: Commentmentioning
confidence: 99%
“…Intracelularmente é convertida pela enzima 5-nucleotidase em dd-IMP (dideoxytinosina 5 monofosfato) que por fim é metabolizada em sua forma ativa dd-ATP (2-3 dideoxyadenosina trifosfato), funcionando como um competidor do substrato dATP da enzima transcriptase reversa viral (inibidor competitivo) (1) .…”
Section: N T R O D U ç ã Ounclassified
“…A neuropatia periférica e a pancreatite são considerados os principais efeitos colaterais dose dependentes da didanosina, ocorrendo geralmente nos primeiros 3 a 6 meses de uso (1) . Casos de retinopatia tóxica em crianças HIV positivas são relatados associados ao uso de altas doses de DDI, porém raros casos são relatados em adultos (2)(3) .…”
Section: N T R O D U ç ã Ounclassified